2022
DOI: 10.1108/jibr-12-2020-0382
|View full text |Cite
|
Sign up to set email alerts
|

Working capital management, financial performance and growth of firms: empirical evidence from India

Abstract: Purpose This paper aims to investigate how firms growing at a high average rate over a period differ in their working capital management (WCM) efficiency from those growing at a low rate during the same period. It also examines how WCM efficiency impacts firms’ financial performance and how firms’ growth influences this relationship. Design/methodology/approach The authors have analyzed the difference in WCM efficiency of a sample of 431 nonfinancial firms during 2012 to 2019 by segregating them into above m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The study revealed that CCC improved shareholder wealth. Utilizing a sample of 431 Indian non-financial firms over eight years (2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019), Sawarni et al (2022) documented that WC efficiency improved firm profitability and value, particularly those that grow at a higher rate.…”
Section: Literature Review and Hypotheses Development 21 A Brief Over...mentioning
confidence: 99%
See 2 more Smart Citations
“…The study revealed that CCC improved shareholder wealth. Utilizing a sample of 431 Indian non-financial firms over eight years (2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019), Sawarni et al (2022) documented that WC efficiency improved firm profitability and value, particularly those that grow at a higher rate.…”
Section: Literature Review and Hypotheses Development 21 A Brief Over...mentioning
confidence: 99%
“…WCM is one of the crucial functions discharged by a financial manager (Ukaegbu, 2014). It is vital in improving firm profitability and liquidity (Nyamao et al ., 2012; Njoroge and Opuodho, 2022; Sawarni et al ., 2022; Urhoghide and Korolo, 2022). In fact, a firm's financial health may be determined by looking at its WCM since the items funded through working capital mostly constitute a significant proportion of their total assets (Le et al ., 2018; Njoroge and Opuodho, 2022; Shurie and Cheluget, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Sawarni et al (2022) measured the efficiency of a sample of 431 nonfinancial firms from 2012 to 2019. The findings indicated that a firm's working capital management significantly impacts its profitability and that working capital management may help businesses increase their profitability.…”
Section: Tangibilitymentioning
confidence: 99%
“…The findings are consistent with the agency theory because high working capital will increase shareholder and management conflict, raising agency costs. Managers will utilize their limited resources more profitably to lower agency costs (Alarussi & Alhaderi, 2018;Tareq et al, 2021;Sawarni et al, 2022).…”
Section: Firmmentioning
confidence: 99%